Feasibility assessment of invigorating grassrooTs primary healthcare for prevention and management of cardiometabolic diseases in resource-limited settings in China, Kenya, Nepal, Vietnam (the FAITH study): rationale and design - Enying Gong; Hongsheng Lu; Shuai Shao; Xuanchen Tao; Nicholas Peoples; Brandon A. Kohrt; Shangzhi Xiong; Catherine Kyobutungi; Tilahun Nigatu Haregu; Christopher Khayeka-Wandabwa; Hoang Van Minh; Tran Thi Duc Hanh; et al. (BMC, 2019)
Abstract Background Cardiometabolic diseases are the leading cause of death and disability in many low- and middle-income countries. As the already severe burden from these conditions continues to increase in low- and middle-income countries, cardiometabolic diseases introduce new and salient public health challenges to primary health care systems. In this mixed-method study, we aim to assess the capacity of grassroots primary health care facilities to deliver essential services for the prevention and control of cardiometabolic diseases. Built on this information, our goal is to propose evidence-based recommendations to promote a stronger primary health care system in resource-limited settings. Methods The study will be conducted in resource-limited settings in China, Kenya, Nepal, and Vietnam using a mixed-method approach that incorporates a literature review, surveys, and in-depth interviews. The literature, statistics, and document review will extract secondary data on the burden of cardiometabolic diseases in each country, the existing policies and interventions related to strengthening primary health care services, and improving care related to non-communicable disease prevention and control. We will also conduct primary data collection. In each country, ten grassroots primary health care facilities across representative urban-rural regions will be selected. Health care professionals and patients recruited from these facilities will be invited to participate in the facility assessment questionnaire and patients' survey. Stakeholders - including patients, health care professionals, policymakers at the local, regional, and national levels, and local authorities - will be invited to participate in in-depth interviews. A standard protocol will be designed to allow for adaption and localization in data collection instruments and procedures within each country. Discussion With a special focus on the capacity of primary health care facilities in resource-limited settings in low- and middle-income countries, this study has the potential to add new evidence for policymakers and academia by identifying the most common and significant barriers primary health care services face in managing and preventing cardiometabolic diseases. With these findings, we will generate evidence-based recommendations on potential strategies that are feasible for resource-limited settings in combating the increasing challenges of cardiometabolic diseases.